Transformasi Petani Rotan (manau) dari Hasil Hutan Kekomoditas perkebunan Rakyat Studi kasus Masyarakat Desa Madobag Kecamatan Siberut Selatan Kabupaten Kepulauan Mentawai 1993-2006 - Hesi, Nurmi; Zusmelia, Zusmelia; Jumhari, Jumhari (Pendidikan Sejarah, 2014)
This thesis describes the transformation of farmers Manau Rattan From Forest Products Into commodities Smallholder economic and social life of the village community Madobag also shape and also influence the transformation of the socio-economic rattan Madobag village from 1993-2006 . This thesis uses historical methods that are arranged in four steps: First heuristic or stage of collecting data and information from multiple sources relevant to utilize primary sources such as documents , Second Critique and external sources for testing and adjustment of the data , three interpretations ( interpretations back ) to explain diporoleh data so as to support this thesis, namely historiography Fourth presentation of research results in the form of scientific writing . From the results of the study showed that the income of villagers who baik.terbukti Madobag changes with the rattan plantation so that the shape transformation walking cane villages madobag well as rattan jungle that was once taken now there diperkebunan people . As well as the socio-economic situation madobag villagers , experiencing changes . These changes can be seen from the level of peoples income and the number of villagers madobag sourced from the agricultural sector . The state of society is more a slight increase from the previous period prior to 1993 because the community relies on the results of rattan from the forest , there are no other jobs in addition to searching the forest rattan cane plantation but after the peoples income has increased from year to year apart from the rattan income people also look for another job apart from gardening rattan and not just a livelihood but already have some work in other words they have to have a side job , so the presence of these people work side earn additional income in Rural peoples social conditions Madobag 1993 as home schools , health , social life and lifestyle has not been so inadequate and no additional buildings